Prevention in Healthcare Practice: An issue with Rising Importance - Raheem, Yousif Abdul (AL-Kindy College Medical Journal, 2020)
Plentiful of healthcare practice is based on a disease/treatment approach rather than a prevention one.  That is, the predominant focus is on treating existing symptoms and conditions that bring the patient to healthcare setting. There is no doubt about the significance of this approach for acute conditions, but there is some question whether this is the most efficient and effective way of distributing healthcare for increasing number of diseases and limited resources.The evidences from everywhere have showed the profound cost benefit of prevention in healthcare practice. Healthy community, therefore, is the ultimate aim in any health services planning. The priority of care giver is shifted now to promote health and prevent disease in any stage (susceptible, subclinical, clinical and recovery/disability) before death, and in all situations, as health status cannot remain constant for an individual, family, community or country over a period of time.